Organisational Factors of Occupational Accidents with Movement Disturbance (OAMD) and Prevention - LECLERCQ, Sylvie (Ind Health, 2014)
Workplace design and upkeep, or human factors, are frequently advanced for explaining so-called Occupational Slip, Trip and Fall Accidents (OSTFAs). Despite scientific progress, these accidents, and more broadly Occupational Accidents with Movement Disturbance (OAMDs), are also commonly considered to be “simple”. This paper aims to stimulate changes in such perceptions by focusing on organisational factors that often combine with other accident factors to cause movement disturbance and injury in work situations. These factors frequently lead to arbitration between production and safety, which involves implementation of controls by workers. These controls can lead to greater worker exposure to OAMD risk. We propose a model that focuses on such controls to account specifically for the need to confront production and safety logics within a company and to enhance the potential for appropriate prevention action. These are then integrated into the set of controls highlighted by work organisation model developed by the NIOSH.